Analisis Yuridis Terhadap Pelaksanaan Perda Nomor 7 Tahun 2012 Tentang RTRW Kabupaten Karimun yang Terbit sebelum Diterbitkan/Disahkan Perda Nomor 1 Tahun 2017 Tentang RTRW Provinsi Kepulauan Riau - Defrita, Maryeni (Journal of Law and Policy Transformation, 2019)
The law is an important instrument in a country. The law is a legal basis that is the basis for the implementation of all policies made by the government. In drafting a regulation, it must be sourced from the rules above so that it cannot be contradictory to the rules above.                This study uses a qualitative method of judicial juridical, juridical imply legal research examines the implementation of positive legal provisions in each particular law. That is reviewing the Spatial Planning Law associated with Regional Regulation Number 7 of 2012 concerning the Karimun Regency Spatial Plan which was issued before the Establishment of Regional Regulation No. 1 of 2017 concerning the Riau Islands Province Spatial Plan.                The results of the study show that in the preparation of spatial plans. according to Article 25 paragraph (1) of the UUPR, the drafting of the Regional Regulations for District Spatial Planning must refer to the provincial spatial plan and the national spatial plan. the issuance of Regional Regulation Number 7 of 2012 concerning Karimun Regency Spatial Planning which was published before the Regional Regulation Number 1 of 2017 concerning the Regional Spatial Plan of Riau Islands Province. Incompatibility was found on maps of space patterns and forest designation between Karimun Regency and Riau Islands Province, resulting in lack of legal certainty. The law is an important instrument in a country. The law is a legal basis that is the basis for the implementation of all policies made by the government. In drafting a regulation, it must be sourced from the rules above so that it cannot be contradictory to the rules above.                This study uses a qualitative method of judicial juridical, juridical imply legal research examines the implementation of positive legal provisions in each particular law. That is reviewing the Spatial Planning Law associated with Regional Regulation Number 7 of 2012 concerning the Karimun Regency Spatial Plan which was issued before the Establishment of Regional Regulation No. 1 of 2017 concerning the Riau Islands Province Spatial Plan.                The results of the study show that in the preparation of spatial plans. according to Article 25 paragraph (1) of the UUPR, the drafting of the Regional Regulations for District Spatial Planning must refer to the provincial spatial plan and the national spatial plan. the issuance of Regional Regulation Number 7 of 2012 concerning Karimun Regency Spatial Planning which was published before the Regional Regulation Number 1 of 2017 concerning the Regional Spatial Plan of Riau Islands Province. Incompatibility was found on maps of space patterns and forest designation between Karimun Regency and Riau Islands Province, resulting in lack of legal certainty.